2018
DOI: 10.1007/s11894-018-0642-9
|View full text |Cite
|
Sign up to set email alerts
|

The Esophageal Microbiome in Health and Disease

Abstract: While the esophagus was previously considered devoid of a significant bacterial population, development of culture-independent techniques, specifically 16S rRNA gene sequencing, as well as novel, minimally invasive microbial sampling modalities, has facilitated characterization of the esophageal microbiome in both health and several disease states. Although limited, there is evidence that the esophagus contains a diverse microbial population, with Gram-positive bacteria, specifically Streptococcus, dominating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…It was shown that the microbial patterns were different from control samples and, interestingly, the bacterial composition changed according to the affected site [35], suggesting that each gastrointestinal cancer has its own microbial signature. Concerning the esophagus, a shift in its microbiome to a less diverse community with dominance of single bacterial species (such as Campylobacter and Lactobacillus) was correlated with esophageal adenocarcinoma [36]. Further, Helicobacter pylori infection is a recognized risk factor for gastric cancer development, but other species from the gastric microbiome are also being associated with carcinogenesis [37].…”
Section: Microbiome and Cancermentioning
confidence: 99%
“…It was shown that the microbial patterns were different from control samples and, interestingly, the bacterial composition changed according to the affected site [35], suggesting that each gastrointestinal cancer has its own microbial signature. Concerning the esophagus, a shift in its microbiome to a less diverse community with dominance of single bacterial species (such as Campylobacter and Lactobacillus) was correlated with esophageal adenocarcinoma [36]. Further, Helicobacter pylori infection is a recognized risk factor for gastric cancer development, but other species from the gastric microbiome are also being associated with carcinogenesis [37].…”
Section: Microbiome and Cancermentioning
confidence: 99%
“…The composition of the microbiome across the GI tract is not uniform, as qualitatively and quantitatively distinct communities have been identified in each ecological and anatomical niche ( Alarcón et al, 2017 ; Proctor and Relman, 2017 ; Gorkiewicz and Moschen, 2018 ; Yadav et al, 2018 ). Research in pets and humans now recognizes distinct microbiomes in the oral cavity ( Dewhirst et al, 2012 , 2015 ; Davis, 2016 ), esophagus ( Corning et al, 2018 ), and stomach ( Bik et al, 2006 ; Gorkiewicz and Moschen, 2018 ). Even within a single anatomical region, evidence in humans and dogs suggests there may be distinct subpopulations that vary with the terrain and topography of the region, as well pH, oxygen, and nutrient gradients ( Suchodolski et al, 2008 ; Segata et al, 2012 ; Wlodarska et al, 2015 ; Hoffmann et al, 2016 ; Honneffer et al, 2017 ; Proctor and Relman, 2017 ; Gorkiewicz and Moschen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the esophagus is regarded as devoid of a significant bacterial population. 1,2 In addition, microbial flora in a normal esophagus has been considered transient and translocated from the oropharynx. 3 In 1998, Gagliardi et al 3 revealed that Streptococcus viridans is the most commonly found microorganism in esophageal cultures, which is also isolated from oropharyngeal cultures.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Additionally, several studies evaluated the microbial composition of a normal esophagus as well as various esophageal diseases such as gastroesophageal reflux disease (GERD), Barrett's esophagus, esophageal cancer, and eosinophilic esophagitis (EoE). 2 Here, we performed a systematic review on the variation in microbial composition according to the esophageal diseases.…”
Section: Introductionmentioning
confidence: 99%